PENGETAHUAN, SIKAP DAN TINDAKAN PETANI DI KABUPATEN TEGAL DALAM PENGGUNAAN PESTISIDA DAN KAITANNYA DENGAN TINGKAT KERACUNAN TERHADAP PESTISIDA - Hidayat, Firman; Khamidi, Tamrin; Wiyono, Suryo (Bumi Lestari; Vol 10 No 1 (2010), 2010)
The objectives of research were to obtain basic information on: 1) pesticide use by Tegal farmers, 2) knowledge, attitude and practices of farmers on pesticide, 3) the relation between knowledge, attitude and practices of farmers on pesticide and intoxication level of farmers. Knowledge-attitude- practice (KAP) survey was conducted on 90 farmers (30 chili farmers, 30 shallot farmers, 30 rice farmers) of Tegal District with structured questionnaire. The information collected included private data, type and number of pesticide uses, knowledge on pesticide, practices and attitude in pesticide uses, and symptom rose after pesticide application. The locations of survey were in Sub-district Surodadi for farmers rice, Dukuhturi for shallot farmers and Bumijawa for chili farmers. The data was grouped and calculated for percentage. Further analysis was conducted by cross tabulation and continued by Ï‡2 test for independence of variables. Five most frequently used pesticides by farmers in Tegal were pesticides with active ingredient chlorpyrifos, profenofos, alphamethrin, deltamethrin and propineb, respectively. Knowledge, attitude and practices of most Tegal farmers on pesticide management is still low and not in line with Integrated Pests Management principles. Moreover, KAP level from the best to the worst was chili farmers, paddy farmers and shallot farmers respectively. Intoxication level based on self report, from the most severe to the least was shallot farmers, chili farmers and paddy farmers respectively. There was significant relation of knowledge and practices of farmers and pesticides intoxication level.